Design e Experiência do Utilizador em Jogos Baseados em Localização para Turismo - Marisa Sofia Martinho Marques (2015)
This thesis intends to study the user experience on a location-based mobile game for tourism as an augmented-reality component.As a development project of a game that is this dissertation, it studies design methodologies for games and interfaces, as well as the overall experience of the interaction for its users. Also, it analyses ways of transmitting contents related to tourism, like discover the history of the city, its monuments, artistic predominance and other touristic related information that are given to users by knowing their exact location. Not to forget that the game's mission also includes learning and fun factors as users explore it.This way, investigation methodologies will be applied, as a functional prototype, which is a location-based game that intends to help new students getting to know the physical space of the school, will be used to evaluate the user experience.This prototype will be applied to a smaller area of the Faculty of Engineering of University of Porto, giving a possibility to study its base features and learning the requirements so that in the future a project like this can be applied in the city of Porto.Keywords: location based games, game design, interface, mobile devices, user experience, usability, tourism, augmented reality, storytelling.